Determinan Manajemen Laba: Bukti Empiris Ukuran Perusahaan, Leverage, dan Tax Planning pada Perusahaan LQ45 Periode 2022–2025 - Wisnu Haryo Pramudya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Earnings management has become a critical issue in financial reporting as it can reduce information quality and mislead investors’ decision-making. Contractual pressures, tax strategies, and firm characteristics are considered key factors influencing managerial incentives to engage in such practices. This study aims to examine the effect of firm size, leverage, and tax planning on earnings management in companies indexed in LQ45 on the Indonesia Stock Exchange during the 2022–2025 period. This research adopts a quantitative approach using secondary data obtained from annual financial reports. The sample consists of 32 companies selected through purposive sampling, resulting in 128 observations. Data analysis was conducted using multiple linear regression with SPSS, including classical assumption tests, coefficient of determination, F-test, and t-test. The results indicate that simultaneously, firm size, leverage, and tax planning have a significant effect on earnings management. Partially, leverage and tax planning have a positive and significant effect on earnings management, while firm size has no significant effect. These findings suggest that contractual pressure and tax planning strategies encourage earnings management practices, whereas stronger monitoring mechanisms in larger firms tend to limit opportunistic behavior. This study contributes to the development of agency theory and provides practical implications for managers, investors, and regulators in improving the quality of financial reporting.